دراسة أثرية لتقنيات و مواد بناء المدينة الرومانية بتيبازة - دحماني مليكة; قبوب لخضر سليم (University of Eloued جامعة الوادي, 2024)
يتمثل هذا العمل في دراسة تشخيصية ميدانية لمواد و تقنيات البناء عند الرومان من خلال معالم المدينة تيبازة الأثرية ،وذلك حسب وفرتها و سهولتها في التنفيذ هذا من جهة ، و من جهة أخرى طبيعة المبنى و وظيفته التي تتحكم في هندسة و طريقة تشييده. كما يعتبر هذا الصرح الأثري شاهد على التطور المعماري الحضاري في الفترة الرومانية ، ويرجع ذلك أصالة مواد البناء المستخدمة و متانة مبانيها إلى يوم هذ. This work is represented in a diagnostic field study of the materials and construction techniques of the Romans through the archaeological monuments of the city of Tipasa, depending on its abundance and ease of implementation, on the one hand, and d on the other hand, the nature of the building and its function which controls the engineering and method of its construction. This archaeological building is also considered as a witness of civilization architectural development in Roman times, due to the originality of the construction materials used and the durability of its buildings to this day
Keywords: مواد; تقنيات; البناء; تيبازة; الاثرية; الرومان; Materials; techniques; construction; Tipasa; the Romans